Noise control in the dental operatory - Po, Henson C.
Noise is a potential health hazard to the dentist, It was found out that noise affects the efficiency of an individual and therefore ways and means must be found to reduce this hazard. To determine where noise comes from, 15 dental clinics were surveyed. It was seen that the noise mainly comes from the handpiece. It was found that the noise levels are in the moderate risk ranges. Furthermore, these sources of noise can be reduced by modifying the handpiece with the use of a body strut made of modelling compound or acrylic or by using a special coupler loosely stuffed with cotton to dampen the sound.